Surface functionalization of reverse osmosis membranes with sulfonic groups for simultaneous mitigation of silica scaling and organic fouling. (15th October 2020) - Guan, Yan-Fang; Boo, Chanhee; Lu, Xinglin; Zhou, Xuechen; Yu, Han-Qing; Elimelech, Menachem
Highlights: Dual functional surface modification of TFC RO membranes with sulfonic groups. Sulfonic groups simultaneously mitigate silica scaling and organic fouling. Sulfonic group imparts high negative surface charge to hinder silica scaling. Sulfonic groups effectively hinder bridging between organic foulant and membrane. Abstract: Organic fouling and inorganic scaling are the main hurdles for efficient operation of reverse osmosis (RO) technology in a wide range of applications. This study demonstrates dual-functionality surface modification of thin-film composite (TFC) RO membranes to simultaneously impart anti-scaling and anti-fouling properties. Two different grafting approaches were adapted to functionalize the membrane surface with sulfonic groups: (i) non-specific grafting of vinyl sulfonic acid (VSA) via redox radical initiation polymerization and (ii) covalent bonding of hydroxylamide- O -sulfonic acid (HOSA) to the native carboxylic groups of the polyamide layer via carbodiimide mediated reaction. Both approaches to graft sulfonic groups were effective in increasing surface wettability and negative charge density of the TFC-RO membranes without significant alteration of water and salt permeabilities. Importantly, we verified through surface elemental analysis that covalently bound HOSA effectively covers the native carboxylic groups of the PA layer. Both the VSA and HOSA membranes exhibited lower flux decline during silica scaling and organic (alginate) fouling relative to the control unmodified membrane, demonstrating the unique versatility of sulfonic groups to endow the TFC-RO membranes with dual functionality to resist scaling and fouling. In particular, the HOSA membrane showed excellent physical cleaning efficiencies with water flux recoveries of 92.5 ± 1.0% and 88.4 ± 6.4% for silica scaling and alginate fouling, respectively. Additional results from silica nucleation experiments and atomic force measurements provided insights into the mechanisms of improved resistance to silica scaling and organic fouling imparted by the surface-functionalized sulfonic groups. Our study highlights the promise of controlled functionalization of sulfonic groups on the polyamide layer of TFC membranes to enhance the applications of RO technology in treatment and reuse of waters with high scaling and fouling potential. Graphical abstract: Image, graphical abstract